Investigation of electric ARC plasma between composite Cu–C electrodes - Veklich, A.N.; Boretskij, V.F.; Ivanisik, A.I.; Lebid, A.V.; Fesenko, S.A. (Вопросы атомной науки и техники, 2013)
Plasma of electric arc discharge in air between composite Cu–C electrodes at arc current 3.5 A in the assumption of local thermodynamic equilibrium was investigated. Special electric device for arc ignition was suggested. The radial profiles of temperature in discharge column were obtained by optical emission spectroscopy. The radial profiles of copper density were obtained by laser absorption spectroscopy. Досліджували плазму електродугового розряду між композитними Cu–C-електродами при силі струму дуги 3,5 А у припущенні локальної термодинамічної рівноваги. Запропоновано спеціальний електронний пристрій для ініціації дугового розряду. Радіальні розподіли температури в розрядному проміжку отримані за допомогою оптичної емісійної спектроскопії. Радіальні розподіли концентрації атомів міді отримані за допомогою лазерної абсорбційної спектроскопії. Исследовали плазму электродугового разряда между композитными Cu–C-электродами при силе тока дуги 3,5 А в предположении локального термодинамического равновесия. Предложено специальное электронное устройство для инициации дугового разряда. Радиальные распределения температуры в разрядном промежутке получены с использованием оптической эмиссионной спектроскопии. Радиальные распределения концентрации атомов меди получены с помощью лазерной абсорбционной спектроскопии.